STRATEGI PEMASARAN MARKETING MIX 7P TERHADAP PENINGKATAN VOLUME PENJUALAN DI ECAPS RESTORAN, KEMANG, JAKARTA - Teresia; Vishnuvardhana S. Soeprapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Business competition in the culinary industry, especially restaurants in strategic areas such as Kemang, Jakarta, requires business actors to implement appropriate marketing strategies in order to increase sales volume. However, there are still obstacles in several elements of the marketing mix that prevent sales from being optimal. This study aims to analyze the implementation of marketing strategies through the 7P marketing mix approach to increase sales volume at Ecaps Restaurant. This study uses a descriptive qualitative research method with a case study approach. The research subjects consist of three key informants: the Head of Marketing, Supervisor, and Sous Chef, who serve as both the population and sample of the study. Data collection techniques were conducted using observation, in-depth interviews, and documentation. Data were analyzed by formulating findings based on the 7P marketing mix elements, which include product, price, place, promotion, people, process, and physical evidence. The results indicate that the Place, Process, and Physical Evidence elements have been implemented effectively and support increased sales volume through strategic location placement, service aligned with standard operating procedures (SOPs), and customer comfort. However, challenges were identified in the Product element, such as unpopular menu items, pricing that has not established a strong value perception, and promotions that have not maximized external collaborations. The People element also faces challenges in human resource management. These findings indicate that the integration of the 7P marketing mix strategy contributes positively but requires regular evaluation of each element to address the dynamics of consumer behavior. This study is expected to serve as a practical reference for culinary business operators in designing adaptive marketing strategies in the era of competitive competition.